Effect of food on environmental safety of natural waters - Поштаренко, А. В. (Problems of Environmental Biotechnology, 2015)
The analysis of the impact of industrial effluents on the ecological state of natural water Ukraine. The main characteristics of wastewater of food enterprises in Ukraine. It indicates the main problems encountered in industrial wastewater treatment and the path to minimize the influence and achievements of ecological safety of the environment.